The Protection of Midazolam Against Immune Mediated Liver Injury Induced by Lipopolysaccharide and Galactosamine in Mice - Li, Jian; Tan, Hong; Zhou, Xiaona; Zhang, Chunpan; Jin, Hua; Tian, Yue; Zhao, Xinyan; Li, Xinmin; Sun, Xuelian; Duan, Meili; Zhang, Dong (Frontiers in Pharmacology, 2019)
Objectives: Liver macrophages agitated by Lipopolysaccharide (LPS) can enhance immuno-inflammatory responses in the liver which mediate liver injury and result in dysfunction. Midazolam has been reported to have inhibitory effects on activated immunity and escalated inflammation, however, what the effects of midazolam on the liver injury caused by excessive immuno-inflammatory response in sepsis, and what influence it will exert on inflamed liver macrophages need to be elucidated. Methods: In the present study, LPS and galactosamine-induced acute liver injury mice were used to observe the effect of midazolam in vivo. LPS-stimulated bone marrow cells were used to evaluate the influence of midazolam on monocytes in vitro. Results: Midazolam ameliorated liver tissue injury and decreased serum alanine transaminase (ALT) level in LPS plus galactosamine treated mice. Mechanistically, midazolam suppressed tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) produced by LPS stimulated liver macrophages in vivo and bone marrow monocytes in vitro, and reduced the expression of major histocompatibility complex class II (MHC II), cluster of differentiation 40 and 86 (CD40 and CD86) on the cell surface. These results could be reversed by PK-11195, a peripheral benzodiazepine receptor (PBR) blocker. Conclusion: Midazolam can prevent liver from LPS-induced immune mediated liver injury by inhibiting inflammation and immune activation in liver macrophages.